Peningkatan Ketrampilan Disain Website Bagi Kelompok Tani Mustika dan Mitra di RPTRA Mustika, Kramat Jati, Jakarta Timur - Eva Magdalena Silalahi; Antonius D. Tyas Prasetyo; Judo Ignatius Nempung; Budiarto; Tahan M.T.N. Lumban Tobing; Dery Elfando (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2025)
The digital literacy skills of MSMEs need to be improved so that MSMEs can increase their product sales through websites. Through websites, MSMEs have control over the sales process. Therefore, this PKM activity is focused on free website design training for the Mustika Farmer Group and its partners in Kamat Jati, East Jakarta. This training is the realization of the MoU of cooperation between the UKI Faculty of Engineering and Kramat Jati Village, East Jakarta in the field of training for the Mustika Farmer Group and partners, in creating websites. This training was held on December 18-19, 2025 at the Mustika RPTRA, Kramat Jati, East Jakarta, attended by 14 participants, which resulted in 6 website designs. This 2-day training received a positive response from participants, who wanted similar training to be held in the future. However, the implementation of this training was not optimal because generally the participants were still classified as newcomers in website design, so they were still confused about starting to design websites again, were not used to surfing the internet, and the training area was near the Halim airport and public sports facilities that were crowded with people, thus disrupting the concentration of the training participants.